Hippocampal Interictal Spikes during Sleep Impact Long‐Term Memory Consolidation. Issue 6 (24th April 2020) - Lambert, Isabelle; Tramoni‐Negre, Eve; Lagarde, Stanislas; Roehri, Nicolas; Giusiano, Bernard; Trebuchon‐Da Fonseca, Agnès; Carron, Romain; Benar, Christian‐Georges; Felician, Olivier; Bartolomei, Fabrice
Abstract : Objective: Non‐rapid eye movement (NREM) sleep is supposed to play a key role in long‐term memory consolidation transferring information from hippocampus to neocortex. However, sleep also activates epileptic activities in medial temporal regions. This study investigated whether interictal hippocampal spikes during sleep would impair long‐term memory consolidation. Method: We prospectively measured visual and verbal memory performance in 20 patients with epilepsy investigated with stereoelectroencephalography (SEEG) at immediate, 30‐minute, and 1‐week delays, and studied the correlations between interictal hippocampal spike frequency during waking and the first cycle of NREM sleep and memory performance, taking into account the number of seizures occurring during the consolidation period and other possible confounding factors, such as age and epilepsy duration. Results: Retention of verbal memory over 1 week was negatively correlated with hippocampal spike frequency during sleep, whereas no significant correlation was found with hippocampal interictal spikes during waking. No significant result was found for visual memory. Regression tree analysis showed that the number of seizures was the first factor that impaired the verbal memory retention between 30 minutes and 1 week. When the number of seizures was below 5, spike frequency during sleep higher than 13 minutes was associated with impaired memory retention over 1 week. Interpretation: Our results show that activation of interictal spikes in the hippocampus during sleep and seizures specifically impair long‐term memory consolidation. We hypothesize that hippocampal interictal spikes during sleep interrupt hippocampal‐neocortical transfer of information. ANN NEUROL 2020;87:976–987